Assessing Cognitive Fatigue in Pediatric Traumatic Brain Injury: Are We Capturing the Whole Picture - Palekar, Pramod; Sukey, Bhargavi; Palekar, Tushar J (Journal of Neonatal Surgery, 2025)
Background: Cognitive fatigue is a common yet underrecognized consequence of pediatric traumatic brain injury (TBI), with significant implications for quality of life, academic performance, and long-term recovery. Despite its prevalence, there is no gold standard for assessing cognitive fatigue in children, and existing tools vary widely in scope and sensitivity. Objective: This scoping review aims to identify and evaluate the outcome measures currently used to assess cognitive fatigue in pediatric TBI populations over the past decade (2014–2024). Methods: Following the PRISMA-ScR guidelines, a systematic search was conducted using PubMed, Scopus, Cochrane, ScienceDirect, and Google Scholar. Studies included focused on children and adolescents with TBI and utilized at least one outcome measure assessing cognitive fatigue. Ten years of literature were reviewed to provide a comprehensive overview of available tools. Results: A total of 10 studies met the inclusion criteria. The most commonly used instrument was the Pediatric Quality of Life Inventory (PedsQL) Multidimensional Fatigue Scale, followed by the PROMIS® Pediatric Fatigue Item Bank and related subjective self- and parent-report tools. These measures primarily captured generalized fatigue, with limited specificity for cognitive domains. Few studies incorporated performance-based or objective assessments. Methodological gaps included heterogeneity in assessment timelines, lack of standardization, and minimal inclusion of younger children or those with severe injuries. Conclusion: Current tools for assessing cognitive fatigue in pediatric TBI populations lack developmental sensitivity, specificity, and ecological validity. There is an urgent need to develop and validate comprehensive, age-appropriate instruments that incorporate both subjective and objective components. Future tools should address fluctuations in cognitive fatigue and support individualized rehabilitation strategies aimed at improving functional outcomes and quality of life